Resozialisierung, Opferschutz, Restorative Justice Grundlagen und Rahmenbedingungen - Bartsch, Tillmann; Hoven, Elisa; Limperg, Bettina; Maelicke, Bernd; Merckle, Tobias (Edition Seehaus [plus] - Resozialisierung - Opferschutz - Restorative Justice, 2023)
Volume 1 of the new publication series Edition Seehaus [plus] explores the three Seehaus themes of rehabilitation, victim protection and restorative justice. The authors analyse current (inter)national developments and the framework conditions for successful resocialization. From the foreword: "An amazing project has taken shape with this first volume (...). "At the interface between science and practice, the newly established Edition Seehaus [plus] is intended to contribute to the development of an evidence-based and sustainable approach to crime and victim protection"; so says a concept paper describing the beginning not only of a book series, but of an overall project that is probably unique in Germany."